Local Markets: Agrobiodiversity Reservoirs and Access Points for Farmers' Plant Propagation Materials - Heindorf, Claudia; Reyes-Agüero, Juan Antonio; van't Hooft, Anuschka (Frontiers in Sustainable Food Systems, 2021)
Local markets are access points to local agrobiodiversity and to part of the informal seed systems on which most small-scale farmers worldwide depend. With the urgent need for more sustainable food systems, detailed studies of the food plant diversity in local markets contribute to a better understanding of the role of local markets in a functioning rural food system. In particular, the products that farmers trade and also use for plant propagation are of interest, i.e., seeds and other propagules such as cuttings, pseudostems, rhizomes, or tubers purposes, since they represent our genetic capital for food production. This study aims to show the role of local markets as access points for plant propagation materials and their contribution to regional in situ conservation of local food plant resources. We analyzed the inter- and intra-specific food plant diversity of the products from local merchants in 10 markets in the agrobiodiversity rich region of the Huasteca Potosina, Mexico. We recorded 275 different food plants consisting of 99 plant species, which have a high intraspecific richness of 210 variants. The list includes 58 species that are useful for propagation. The average number of variants suitable for propagation at each market is 58.4. The results show that the different richness parameters vary within and between the inventoried markets. They correlate partially to different factors like market size and origin. We conclude that local markets in the Huasteca Potosina are important components of the rural food system by providing access to a great variety of local food plants, as well as to seeds and other propagation materials for farming. However, diversity may be threatened, because of the high average proportion of unique and rare food plants (63.5%) in the markets. Also, almost half (45.1%) of the total richness is present in <1% of the inventoried stands. Political actions are needed to maintain and promote the use and conservation of this diversity in the future.